Kajian Hukum terhadap Akibat Merger Perusahaan Terbuka dalam Sistem Hukum Bisnis Indonesia - Cindy Dwiyanti (Jurnal Hukum Lex Generalis, 2025)
Merger of public companies is a strategic instrument in corporate restructuring that not only improves business efficiency but also has significant legal implications for shareholders, creditors, and third parties. This research examines the legal impact of mergers of public companies in Indonesia using a normative legal method, analyzing regulations such as the Limited Liability Companies Law, the Capital Markets Law, the Prohibition of Monopolistic Practices Law, and OJK regulations governing merger mechanisms. The research findings indicate that although the legal framework for mergers is procedurally quite comprehensive, there are still significant weaknesses in substantive aspects, particularly in the protection of minority shareholders, creditors, and third-party rights. The appraisal rights of minority shareholders are less effective, creditors often lack adequate protection, and third parties face contractual uncertainty due to change of control clauses. This research recommends regulatory harmonization, strengthening coordination between the Financial Services Authority (OJK) and the Business Competition Supervisory Commission (KPPU), and adopting international practices such as tag-along rights and mandatory mediation to create a more transparent, adaptable, and just business legal system in Indonesia.